Titanium Nanoparticle Size Influences Trace Concentration Levels in Skin Appendages. (July 2017) - Tasat, Deborah R.; Domingo, Mariela G.; Bruno, Marcos E.; Guglielmotti, María B.; Olmedo, Daniel G.
As a result of biotribocorrosion, the surface of a titanium (Ti) biomedical device can be a potential source of systemic contamination with Ti nanoparticles (NPs). Although NPs can be chemically similar, differences in particle size may lead to different biological responses. The aim of this experimental study was to determine Ti trace levels in skin appendages and plasma and explore the influence of NP size on trace levels using a murine model. Results showed the presence of Ti traces in the nails, hair, and plasma. The concentration of the smallest NPs (5 Nm) was higher than that of 10 Nm NPs in all the studied samples. Irrespective of NP size, Ti levels were always lower in plasma than in skin appendages. Ti levels were higher in nails than in hair. Ti NPs size influenced trace concentration levels in hair/nails, suggesting that 5 Nm Ti particles are more easily eliminated through these skin appendages. Given that the nails showed the highest levels of Ti, and that these skin appendages are not exposed to agents that can leach out Ti, as occurs with hair, we propose the nails as the most suitable and reliable bioindicator for monitoring systemic contamination with Ti.